1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Posted by Joseph Georgeabout 2 hours ago (l+3)(b-4) = lb - 67 lb - 4l + 3b - 12 = lb - 67 -4l + 3b = -55 it can also be written as 4l-3b = 55 ---(1) (l-1)(b+4) = lb + 89 lb +4l - b +4 = lb +89 4l - b = 85 ---(2) subtracting 2 from 1 4l - 4l -3b +b = 55 - 85 -2b = -30 b = 15 putting this in 1 4l - 3(15) = 55 4l - 45 = 55 4l = 100 l= 25 lenght = 25 m bredth = 15 m..see this was the solution sir and i want to ask that (l-1)(b+4) openings means how to open it ..my ans is coming as-4 but here +4.plz clear itttt

Open in App
Solution

## A slight correction. Opening the (l-1)(b+4) gives => lb + 4l -b -4 = 89 + lb 4l - b = 93 ...(2) Subtracting 2 from 1 4l - 4l -3b +b = 55 - 93 -2b = -38 b = 19 cm Given in (2) 4l - b = 93 => 4l - 19 = 93 4l = 112 l = 112/4 l = 28 cm Therefore b = 19cm and l = 28cm

Suggest Corrections
1
Join BYJU'S Learning Program
Related Videos
Algebraic Solution
MATHEMATICS
Watch in App
Join BYJU'S Learning Program